Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 64513 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Equisetum sylvaticum L." ] } The dataset includes 64513 records from 308 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0081948-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences